DYNAMICS OF WOODY SPECIES IN DRY TROPICAL FOREST (CAATINGA), BRAZIL - Barreto, Thyêgo Nunes Alves; Ferreira, Rinaldo Luiz Caraciolo; Silva, José Antônio Aleixo; almeida, cleuma christir da silva; Pinto, Andréa de Vasconcelos Freitas (Floresta, 2020)
Studying selected floristic changes in dry forests is fundamental to foster conservation and sustainability strategies. Objective: to analyze the occurrence of woody species in a tropical forest with a history of use. In 2008, 40 permanent plots were installed and wood with a circumference of 1.30 m at a breast height (CAP) ≥ 6 cm were measured. In 2012, newly established individuals (those that did not meet the size requirements in 2008 but did in 2012) and mortality of the remaining individuals were analyzed by computer. Where applicable, the density, frequency, and absolute dominance, importance value, newly established individuals, mortality, and gross growth for each species, along with the Shannon index were estimated. The floristic composition and diversity remain unchanged. After four years, there were few differences between species, while in most cases the growth in the basal area was positive and sometimes the number of newly established individuals exceeded the mortality. After 24 years of logging, the analyzed forest area did not reach its initial basal area stock when compared to other areas of the Caatinga that do not have a history of disturbance.